MOG-IgG-Associated Optic Neuritis, Encephalitis, and Myelitis: Lessons Learned From Neuromyelitis Optica Spectrum Disorder - dos Passos, Giordani Rodrigues; Oliveira, Luana Michelli; da Costa, Bruna Klein; Apostolos-Pereira, Samira Luisa; Callegaro, Dagoberto; Fujihara, Kazuo; Sato, Douglas Kazutoshi (Frontiers in Neurology, 2018)
Antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) have been found in some cases diagnosed as seronegative neuromyelitis optica spectrum disorder (NMOSD). MOG-IgG allowed the identification of a subgroup with a clinical course distinct from that of NMOSD patients who are seropositive for aquaporin-4-IgG antibodies. MOG-IgG is associated with a wider clinical phenotype, not limited to NMOSD, with the majority of cases presenting with optic neuritis, encephalitis with brain demyelinating lesions, and/or myelitis. Therefore, we propose the term MOG-IgG-associated Optic Neuritis, Encephalitis, and Myelitis (MONEM). Depending on the clinical characteristics, these patients may currently be diagnosed with NMOSD, acute disseminated encephalomyelitis, pediatric multiple sclerosis, transverse myelitis, or optic neuritis. With specific cell-based assays, MOG-IgG is emerging as a potential biomarker of inflammatory disorders of the central nervous system. We review the growing body of evidence on MONEM, focusing on its clinical aspects.